Peroxisome proliferator activated receptor gamma controls mature brown adipocyte inducibility through glycerol kinase - Lasar, David (2018)
Peroxisome proliferator-activated receptors (PPARs) have been suggested as the master regulators of adipose tissue formation. However, their role in regulating brown fat functionality has not been resolved. To address this question, we generated mice with inducible brown fat-specific deletions of PPARα, β/δ, and γ, respectively. We found that both PPARα and β/δδ are dispensable for brown fat function. In contrast, we could show that ablation of PPARγ in vitro and in vivo led to a reduced thermogenic capacity accompanied by a loss of inducibility by β-adrenergic signaling, as well as a shift from oxidative fatty acid metabolism to glucose utilization. We identified glycerol kinase (Gyk) as a partial mediator of PPARγ function and could show that Gyk expression correlates with brown fat thermogenic capacity in human brown fat biopsies. Thus, Gyk might constitute the link between PPARγ-mediated regulation of brown fat function and activation by β-adrenergic signaling.